Reply to Comment by Vincent et al. Issue 3 (25th March 2018) - Cowgill, Eric; Niemi, Nathan A.; Forte, Adam M.; Trexler, Charles C.
Key Points: The Greater Caucasus Basin encompassed a broader region than envisioned by Vincent et al., who disregard Cenozoic shortening Terminal basin closure occurred when the Greater and Lesser Caucasus collided Data cited by Vincent et al. document the onset of basin closure by 35 Ma, but do not indicate terminal basin closure at this time